Impact of COVID-19 on Consumption Pattern of Vegetarians and Non-Vegetarians - M. B. Shanabhoga,; Gurrappanaidu Govindaraj, G. S. Naveenkumar, H. M. Swamy, Mahantheshwara Bheemappa, M. Nagalingam, B. R. Shome and Habibar Rahman, (Indian Journal of Extension Education, 2022)
The aim of this study was to investigate the impacts of COVID-19 on the consumption patterns of vegetarians and non-vegetarian populations, mainly on animal-based products. A cross-sectional, questionnaire-based survey was conducted among the urban and periurban populations of Bengaluru, Karnataka during October to November of 2020 through electronic mode. The data was collected from 837 (54.2% non-vegetarian and 54.2% vegetarians) participants. Significant change in the number of family members before and during the COVID lockdown was observed. The egg and chicken consumption had drastically increased among the non-vegetarians whereas, among the majority of the vegetarians, no change in milk consumption but a considerable increase in curd and buttermilk, paneer/cheese, and ghee/butter consumption was observed. Both non-vegetarian and vegetarian consumers had shifted to online delivery apps for purchasing products during the pandemic. The majority of the non-vegetarians (80.84%) and vegetarians (55.09%) opined that the price of meat and milk products increased during the pandemic. The pandemic had an effect on consumption among non-vegetarian and vegetarian consumers but increased accessibility of products through deliveries or pick-up points at various locations might have reduced the price and also induce the consumption of these products.